Peptide‐MHC class I and class II tetramers: From flow to mass cytometry. (23rd January 2020) - Christophersen, Asbjørn
Abstract : To develop better vaccines and more targeted treatments for cancer and autoimmune disorders, the disease‐specific T cells and their cognate antigens need to be better characterized. For more than two decades, peptide‐major histocompatibility complex (pMHC) tetramers and flow cytometry have been the gold standard for detection of CD8+ and CD4+ T cells specific to antigens in the context of MHC class I and class II, respectively. Nonetheless, more recent studies combining such reagents with mass cytometry, that is, cytometry by time of flight (CyTOF), have offered far more comprehensive profiling of antigen‐specific T‐cell responses. In addition, mass cytometry has enabled ex vivo screening of CD8+ T‐cell reactivities against hundreds of MHC class I restricted candidate epitopes. MHC class II molecules, on the other hand, have been challenging to combine with mass cytometry as they are more complex and bind with lower affinities to cognate T‐cell receptors than MHC class I molecules. In this review, I discuss how techniques originally developed to improve the staining capacity of pMHC tetramers in flow cytometry led to the successful combination of such reagents with mass cytometry. Especially, I will highlight very recent advances facilitating the combination with pMHC class II tetramers. Together, these mass cytometry‐based studies can help develop more targeted treatments for cancer and autoimmune disorders.